Supporting teacher educator professional learning about assessment: Insights from the design and use of a task analysis tool in a first year BEd programme - Dixon, K.; Reed, Y.; Reid, J. (South African Journal of Higher Education, 2016)
While there is an extensive literature in the field of professional development for teachers, much less has been researched and written about professional development for teacher educators (Smith, 2003). In this article we present and discuss findings from an assessment research project in the School of Education at the University of the Witwatersrand which offered opportunities for professional development to teacher educators in a B Ed programme. The research project focussed on first year assignments and examinations because of concerns about the underpreparedness of many first year students for the cognitive and academic literacy challenges of university study. We present a tool for the analysis of formative and summative assessment tasks and then describe and discuss its use in the analysis of (i) a first year assignment and (ii) a first year examination question. In the concluding section we argue firstly, that the collaborative design and use of the task analysis tool enabled professional learning for teacher educators and secondly, that such learning can lead to the adoption of assessment practices that both transmit criteria of knowledge being taught and test students mastery of these criteria at an appropriate cognitive and academic literacy level.